Effects of the herbicide surfactant MON 0818 on oviposition and viability of eggs of the ramshorn snail (Planorbella pilsbryi). (19th September 2016) - Prosser, Ryan S.; Rodriguez‐Gil, Jose L.; Solomon, Keith R.; Sibley, Paul K.; Poirier, David G.
Abstract: The surfactant mixture MON 0818 is an adjuvant in various commercial formulations of the herbicide glyphosate. Initial studies have shown that MON 0818 is more toxic to aquatic animals than the active ingredient. However, few studies have examined the effect of exposure to MON 0818 on species of mollusks, and no studies have examined the effect on gastropods. The present study investigated the effect of acute exposure (96 h) of MON 0818 to the eggs, juveniles, and adults of the file ramshorn snail ( Planorbella pilsbryi ). Concentrations of MON 0818 up to 9.9 mg/L did not have a significant effect on the viability of eggs ( p > 0.05). Juvenile snails (50% lethal concentration [LC50] = 4.0 mg/L) were more sensitive than adult snails (LC50 = 4.9–9.1 mg/L). Oviposition was inhibited by exposure to MON 0818 (median effective concentration [EC50] = 0.4–2.0 mg/L). However, oviposition resumed when snails were removed to clean water, even after 96‐h exposure to up to 4.9 mg/L of MON 0818. Exposure to a concentration ≥2.7 mg/L caused visible damage to the tentacles of adult snails, which could potentially impact chemoreception. A deterministic hazard assessment indicated that environmentally relevant concentrations of MON 0818 could pose a hazard to the deposition of eggs. However, because of the relatively short half‐life of MON 0818 in aquatic systems and the ability of snails to resume oviposition following the dissipation of MON 0818, environmentally relevant concentrations of MON 0818 likely pose a de minimis risk to populations of ramshorn snails. Environ Toxicol Chem 2017;36:522–531. © 2016 SETAC